1960
DOI: 10.1083/jcb.7.4.743
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Observations on the Three-Dimensional Morphology of Apatite Crystallites of Human Dentine and Bone'

Abstract: In sections of human dentine (carious and sound) and bone examined with the electron microscope, apatite crystallites were seen to present long thin profiles somewhat suggestive of a cylindrical shape, broad profiles indicative of a plate-like shape, and profiles intermediate between these two extremes. With a special stereoscopic specimen holder allowing the specimen to be tilted through an angle of 30 ° it was possible to record images of two profiles of the same crystallite from different angles and thus ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

1969
1969
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(34 citation statements)
references
References 8 publications
3
30
0
Order By: Relevance
“…6 it can be seen that the particles appear to be plates, whereas some of the earlier works on this topic regard the mineral crystals as needle-like [20]. However, the existence of bone mineral in plate-like crystals has been noted previously [21]. Bocciarelli [10] showed transmission electron micrographs (TEMs) of ox bone which demonstrate both needle-like and plate-like crystals, and after considering the contrast difference in micrographs, the author concluded that the needles are in fact edge views of plates as opposed to the view that plates could be aggregates of needles [20].…”
Section: Discussionmentioning
confidence: 78%
“…6 it can be seen that the particles appear to be plates, whereas some of the earlier works on this topic regard the mineral crystals as needle-like [20]. However, the existence of bone mineral in plate-like crystals has been noted previously [21]. Bocciarelli [10] showed transmission electron micrographs (TEMs) of ox bone which demonstrate both needle-like and plate-like crystals, and after considering the contrast difference in micrographs, the author concluded that the needles are in fact edge views of plates as opposed to the view that plates could be aggregates of needles [20].…”
Section: Discussionmentioning
confidence: 78%
“…1a and b) columns running through the tissue. The rest of the matrix of dentine is stiffened by cHAp particles (Johansen and Parks, 1960) protein nanofibrils (Jantou- Morris et al, 2010;McNally et al, 2012). The mineral and fibres combine to form the mineralized collagen fibre matrix of dentine ("intertubular dentine"), which resembles the matrix found in other members of the bone family of materials (Weiner and Wagner, 1998).…”
Section: Introductionmentioning
confidence: 97%
“…The complex structure of human teeth [28][29][30][31][32] facilitates the preservation of hardness and wear resistance over many millions of masticatory cycles. Besides the microscopic structure, investigations of the nanostructure have been performed, mainly with local probe techniques including atomic force microscopy (AFM) and scanning electron microscopy (SEM) [22,[33][34][35][36]. Due to the reduced field of view, however, only restricted parts of the tooth of interest can be examined.…”
Section: Introductionmentioning
confidence: 99%